The impact of nutrition on injury prevention and rehabilitation - Dr Amarjeet Singh (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
The role of nutrition in injury prevention and rehabilitation is an emerging field that holds significant promise for enhancing athletic performance, expediting recovery, and improving overall health outcomes. This paper explores the multifaceted impact of nutrition on injury prevention and rehabilitation, drawing on current research and clinical evidence. Proper nutrition is critical for maintaining tissue health, reducing inflammation, and facilitating the repair and regeneration of damaged tissues. Macronutrients such as proteins, carbohydrates, and fats, as well as micronutrients including vitamins and minerals, play specific roles in supporting the body's healing processes. Anti-inflammatory foods and adequate hydration further contribute to reducing injury risk and promoting recovery. The integration of nutritional strategies into injury prevention and rehabilitation protocols can optimize the recovery timeline, reduce downtime, and enhance long-term health and performance. This paper aims to provide a comprehensive overview of the key nutrients and dietary strategies that are essential for injury prevention and rehabilitation, offering practical guidelines for healthcare providers, sports professionals, and individuals seeking to optimize their recovery through nutrition.